Film and the Chinese Medical Humanities - Lo, Vivienne; Berry, Chris; Liping, Guo (Taylor & Francis, 2019)
Film and the Chinese Medical Humanities is the first book to reflect on the power of film in representing medical and health discourse in China in both the past and the present, as well as in shaping its future. Drawing on both feature and documentary films from mainland China, the chapters each engage with the field of medicine through the visual arts. They cover themes such as the history of doctors and their concepts of disease and therapies, understanding the patient experience of illness and death, and establishing empathy and compassion in medical practice, as well as the HIV/AIDs epidemic during the 1980s and 90s and changing attitudes towards disability. Inherently interdisciplinary in nature, the contributors therefore provide different perspectives from the fields of history, psychiatry, film studies, anthropology, linguistics, public health and occupational therapy, as they relate to China and people who identify as Chinese. Their combined approaches are united by a passion for improving the cross-cultural understanding of the body and ultimately healthcare itself.